The Effect of Collaborative Asynchronous E-mailing on EFL Learners' Writing Ability - Ezzat Barghi (Applied Linguistics Research Journal, 2018)
The present study attempted to discover the impact of collaborative learning through e-mail on the improvement of the writing ability of Iranian advanced level EFL learners. In order to have homogeneous groups, all 40 participants of the study were administered a TOEFL proficiency test, and then they were randomly assigned to comparison and experimental groups. Since the study concentrated on writing ability a writing pretest was administered to both groups to make sure they were also homogeneous in terms of writing ability. In the comparison group, the participants were asked to write their paragraphs individually, while the participants of the experimental group were supposed to write their paragraph collaboratively through e-mail. After 10 sessions of treatment, a writing posttest was administered to both groups. The results of related statistics indicated that the participants of the experimental group had a significantly better performance in their writing ability compared to the comparison group. It was concluded that collaborative e-mailing might improve the writing ability of EFL learners. The implication of the study for syllabus designers and language teachers is to include e-learning techniques and activities if they wish for their learners' enthusiasm for learning activities.